Maternal Obesity Programming of Perivascular Adipose Tissue and Associated Immune Cells: An Understudied Area With Few Answers and Many Questions - Corken, Adam; Thakali, Keshari M. (Frontiers in Physiology, 2022)
At present, the worldwide prevalence of obesity has become alarmingly high with estimates foreshadowing a continued escalation in the future. Furthermore, there is growing evidence attributing an individual’s predisposition for developing obesity to maternal health during gestation. Currently, 60% of pregnancies in the US are to either overweight or obese mothers which in turn contributes to the persistent rise in obesity rates. While obesity itself is problematic, it conveys an increased risk for several diseases such as diabetes, inflammatory disorders, cancer and cardiovascular disease (CVD). Additionally, as we are learning more about the mechanisms underlying CVD, much attention has been brought to the role of perivascular adipose tissue (PVAT) in maintaining cardiovascular health. PVAT regulates vascular tone and for a significant number of individuals, obesity elicits PVAT disruption and dysregulation of vascular function. Obesity elicits changes in adipocyte and leukocyte populations within PVAT leading to an inflammatory state which promotes vasoconstriction thereby aiding the onset/progression of CVD. Our current understanding of obesity, PVAT and CVD has only been examined at the individual level without consideration for a maternal programming effect. It is unknown if maternal obesity affects the propensity for PVAT remodeling in the offspring, thereby enhancing the obesity/CVD link, and what role PVAT leukocytes play in this process. This perspective will focus on the maternal contribution of the interplay between obesity, PVAT disruption and CVD and will highlight the leukocyte/PVAT interaction as a novel target to stem the tide of the current obesity epidemic and its secondary health consequences.